2009
DOI: 10.1002/eat.20675
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of a Fijian translation and adaptation of the Eating Disorder Examination Questionnaire

Abstract: Objective:Assessment of disordered eating has uncertain validity across culturally diverse populations. This study evaluated Eating Disorder Examination Questionnaire (EDE-Q) performance in an ethnic Fijian study population.Method:The EDE-Q was translated, adapted, and administered to school-going Fijian adolescent females (N = 523). A subsample (n = 81) completed it again within ∼1 week. We assessed feasibility, internal consistency, and test-retest reliability; evaluated construct validity through factor ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
85
3
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 16 publications
14
85
3
2
Order By: Relevance
“…In addition to these recognizable features as potential consequences of globalization, Becker et al recently found that 35% of Fijian school girls ages 15 to 20 years endorsed traditional herbal purgative use. 56 Follow-up analyses indicated that traditional herbal purgative use was associated with significantly elevated impairment and distress in these girls, 57 supporting the value of culture-specific assessments to enhance detection of eating disorder symptoms in non-Western contexts. 56 However, Becker 54 cautioned that syndromes identified within a Western context may not be represented in a comparable indigenous illness category.…”
Section: Who Most Likely Presents With Purging Disorder?mentioning
confidence: 90%
See 2 more Smart Citations
“…In addition to these recognizable features as potential consequences of globalization, Becker et al recently found that 35% of Fijian school girls ages 15 to 20 years endorsed traditional herbal purgative use. 56 Follow-up analyses indicated that traditional herbal purgative use was associated with significantly elevated impairment and distress in these girls, 57 supporting the value of culture-specific assessments to enhance detection of eating disorder symptoms in non-Western contexts. 56 However, Becker 54 cautioned that syndromes identified within a Western context may not be represented in a comparable indigenous illness category.…”
Section: Who Most Likely Presents With Purging Disorder?mentioning
confidence: 90%
“…56 Follow-up analyses indicated that traditional herbal purgative use was associated with significantly elevated impairment and distress in these girls, 57 supporting the value of culture-specific assessments to enhance detection of eating disorder symptoms in non-Western contexts. 56 However, Becker 54 cautioned that syndromes identified within a Western context may not be represented in a comparable indigenous illness category. In particular, although Fijian girls endorse using herbal purgatives to compensate for feasts that do not involve consumption of more food than most people eat in that context, this behavior is not always associated with distress and has not been identified as an ''emic'' (from within the local group) disorder.…”
Section: Who Most Likely Presents With Purging Disorder?mentioning
confidence: 90%
See 1 more Smart Citation
“…Em âmbito internacional, os estudos de validação dos instrumentos utilizados pelos sistemas de vigilância dirigidos a adolescentes englobam módulos específicos como transtornos alimentares 12 , atividade física 13,14,15 e práticas alimentares 16,17,18 .…”
Section: Introductionunclassified
“…Many validated English-language questionnaires have been successfully translated into the vernacular, with the obvious intent of including the maximum number of patients. 9,10 Hence, our 11-question set was translated into Malayalam, the language spoken by the people of the state of Kerala, where our institution is situated. We already have experience with a validated Malayalam voice handicap index 30, which is one of the standard questionnaires used in voice disorders.…”
Section: Typementioning
confidence: 99%